THE INFLUENCE OF LUEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMACE AT CV WIRA AMERTA - Sugiyanto; Nuryadi (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2025)
This study aims to analyze the influence of leadership style and organizational culture on employee performance. This study used a sample of 16 respondents who had worked for approximately three years. Data were collected through questionnaires, observation, and documentation. Data analysis techniques used SPSS, including validity tests, reliability tests, normality tests, multicollinearity tests, multiple linear regression analysis, and hypothesis testing. The results showed that leadership style and organizational culture influence employee performance.